ANALISIS TERHADAP FAKTOR YANG MEMICU MUNCULNYA KULTUSISME TERHADAP TOKOH AGAMA MELALUI PENDEKATAN SOSIOLOGI : KAJIAN LITERATUR: Indonesia - Leo Farid Ruhiana; Mirna Nur Alia Abdullah; Muhammad Retsa Rizaldi Mujayapura (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2025)
The phenomenon of cultism toward religious figures continues to persist despite the entrance of society into an era of cultural modernism, which is characterized by rationality and scientific advancement. This article aims to analyze the factors that trigger the emergence of cultism toward religious leaders through a sociological approach and to explain its influence on modern social life. The method used is a literature review of various scholarly sources, including academic journals and research articles relevant to the theme of cultism in society. The study's findings indicate that cultism arises as a response to socio-economic instability experienced by communities, where the presence of charismatic figures is seen as a beacon of hope for prosperity and liberation from hardship. Society tends to seek authoritative figures who offer certainty in social life. Additionally, the influence of media, feudalistic social structures, and power relations between religious figures and their followers further reinforce this phenomenon. Cultural modernism and the shift toward more moderate religious values do not automatically eliminate cult practices; rather, they transform them into more symbolic and concealed forms. This study recommends the importance of critical religious literacy and the strengthening of social rationality to prevent distortions in the relationship between religious leaders and society.